2006
DOI: 10.1155/ijrm/2006/17379
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of a Radial Turbine Using Pitch‐ControlledGuide Vanes for Wave Power Conversion

Abstract: In order to develop a high-performance radial turbine for wave power conversion, a radial turbine with pitch-controlled guide vanes has been proposed and manufactured in the study. The proposed radial turbine has been investigated experimentally by model testing under steady and sinusoidal flow conditions. Then, the experimental results have been compared with those of the conventional radial turbine for wave power conversion, that is, a radial turbine with fixed guide vanes. As a result, the running character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Setoguchi et al [4] conducted an experimental parametric study for the radial turbine varying the inner and outer guide vane angles recommending a 25° orientation for the vanes. Further studies were proposed by Takao et al (2005) [5] investigating the effect of using pitch-controlled guide vanes and found an increase by 15% compared to fixed guide vanes. Various numerical studies performed on radial turbine by B. Pereiras et al [6] modeled a new radial impulse turbine geometry after validating it with previous experimental work [4].…”
Section: Introductionmentioning
confidence: 99%
“…Setoguchi et al [4] conducted an experimental parametric study for the radial turbine varying the inner and outer guide vane angles recommending a 25° orientation for the vanes. Further studies were proposed by Takao et al (2005) [5] investigating the effect of using pitch-controlled guide vanes and found an increase by 15% compared to fixed guide vanes. Various numerical studies performed on radial turbine by B. Pereiras et al [6] modeled a new radial impulse turbine geometry after validating it with previous experimental work [4].…”
Section: Introductionmentioning
confidence: 99%